Invasive micropapillary breast carcinoma: A retrospective study on the clinical imaging features and pathologic findings - Nangong, Jiarui; Cheng, Zhongquan; Yu, Leyi; Zheng, Xiaodan; Ding, Guoqian (Frontiers in Surgery, 2022)
Purpose: To describe the clinical imaging and pathological features of invasive micropapillary breast carcinoma (IMPC), including breast mammography, sonography, magnetic resonance imaging (MRI), and molecular imaging findings. Patients and Methods: We retrospectively reviewed our institution’s surgical pathology database and identified 65 patients with pathologically proven IMBC; 63/65 patients had available imaging results. Two radiologists retrospectively reviewed all imaging evaluations according to the Breast Imaging Reporting & Data System (BI-RADS) Lexicon. Clinical and histopathologic features, receptor statuses, and clinical follow-up data were recorded. Results: Sixty-three patients were admitted with palpable abnormalities; one patient’s mammogram revealed no abnormality (3.3%, 1/32), whereas 31 had abnormal mammograms (31/32，96.8%) demonstrating 37 lesions. Twenty-four had irregular, spiculated masses, 12 had microcalcifications, and 19 had architectural distortion. Sonography detected 69 masses (54 patients), characterized by irregular shapes (61/69, 88.4%), hypoechoic structures (50/69, 72.4%), angular or spiculated margins (38/69, 55.1%; 30/69, 43.4%), echogenic halo (8/69, 11.5%), and abnormal vascularity (52/69, 75.3%). MRI detected 68 lesions (52 patients); 59/68 (86.8%) appeared as masses with angular or spiculated margins (32/68, 47.1%; 35/68, 51.4%), 58 exhibited irregular or lobulated shapes (58/68, 89.7%), 29 displayed heterogeneous internal enhancement (29/68, 42.5%), and 64 demonstrated type II or III washout kinetic curves (37/68, 55%; 27/68, 40%). Breast molecular imaging showed mild-to-moderate radiotracer uptake in 15 focal areas among 13 patients. Thirty-two, 38, and 43 patients had abnormal lymph nodes identified mammographically, by breast sonography, and by MRI, respectively. Immunohistochemistry revealed high estrogen receptor (90.5%), high progesterone receptor (71.6%), and low HER-2 (26.4%) positivity. Conclusion: IMPC mammography, sonography, and MRI clinical imaging features highly suggest malignancy. Breast molecular imaging also contributed to the diagnosis. IMPC’s invasiveness correlated well with regional lymph node metastasis. Radiologists and surgeons should be more attentive to these imaging findings and additional clinical and pathological IMPC features.